OPTIMASI MANAJEMEN KURIKULUM: INTEGRASI RINCIAN PEKAN EFEKTIF DAN ANALISIS KOMPETENSI DALAM TRANSFORMASI PENDIDIKAN ERA 4.0 - Eni Sri Wahyuni; Nurannisa Ridwan; Al Yumna Istiqamah A; Takdirmin (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Effective curriculum management is the backbone of educational quality in the Era 4.0. This non-empirical article aims to examine the integration between Effective Week Details (RPE) and the analysis of Basic Competencies (KD) or Learning Outcomes (CP) as a strategic step in academic planning. The method used is a conceptual literature review involving systematic searching and synthesis of relevant sources. The findings indicate that precise time mapping through RPE, synchronized with material weight analysis, prevents curriculum lag and ensures depth of learning. This article emphasizes that such integration is essential for teachers to navigate the dynamic challenges of modern education.